COMMUNITY PERCEPTION AND PARTICIPATION TOWARDS THE JANGKA BENAH PROGRAM IN WEST TANJUNG JABUNG - Rince Muryunika; Fazriyas; Bambang Irawan; Riana Anggraini; Khairun Nisa (Jurnal Belantara, 2026)
The existence of expanding oil palm plantations is inevitable, as it has contributed significantly to increasing household incomes. However, the continued practice of monoculture oil palm plantations in forest areas poses a critical challenge to the sustainability of the ecosystem. This study aims to analyze farmers’ perceptions and participation in oil palm-based agroforestry management, as well as the relationship. Data collection was conducted through interviews, data were analyzed using a descriptive qualitative approach and a quantitative approach using Chi Square. The variables studied were farmer perception (X) and farmer participation (Y).The study population consisted of members of Forest Farmer Groups (KTH) in the Jangka Benah program a collaborative effort between the Forest Management Unit (KPHP) Unit XVI Tanjung Jabung Barat and the Natural Resources Conservation Agency (BKSDA) of Jambi Province. This program was implemented in Sungai Penoban Village and involved three farmer groups: KTH Anugerah, KTH Bukit Indah, and KTH Tri Jaya Makmur. The results of the study indicate that although farmers generally have positive perceptions, but the farmer participation is very low. The results of the Chi-Square test indicate that there is no significant relationship between perception and participation in Jangka Benah programs (0.406) with a contingency degree of 0.1 (very weak). The main factor influencing this reluctance was concern over potential economic risks, especially the perceived threat of reduced oil palm productivity. In addition, poor growth of intercrops planted three years earlier further hampered participation, ultimately leading most farmers to discontinue agroforestry practices in their oil palm plantations.